A preliminary checklist of fireflies (Coleoptera: Lampyridae) with two new distribution records from Sarawak - Nurfarida Anum Zainaddin; Siti Nurlydia Sazali (Penerbit Universiti Kebangsaan Malaysia, 2023)
The remarkable ability of fireflies for bioluminescence makes them one of the most charismatic species of beetles. Despite the increasing development and urbanisation especially in mangrove areas, the current status of fireflies in Sarawak is not well documented. Hence, this study aims to provide an updated preliminary checklist focusing on the firefly species from Sarawak, Malaysia to contribute to the scientific knowledge of Lampyridae. Twenty localities in Sarawak were selected as the sampling sites based on firefly sightings. Field surveys were carried out from October 2022 to February 2023 with additional samples obtained from the UNIMAS Insect Reference Collection (UIRC). The present study recorded a total of 372 individuals of fireflies representing five genera, namely Pteroptyx (with five species and two morphospecies), Pyrocoelia (with one species and one morphospecies), Luciola (with two species), Colophotia (with one species) and Abscondita (with one species). The first record of two species Colophotia brevis (Luciolinae) and Pyrocoelia opaca (Lampyrinae) in Sarawak was documented in this study. Thus, it is suggested that a more comprehensive study, especially in the central region of Sarawak alongside its preferred host trees should be conducted. This information will provide a better understanding of firefly habitats in Sarawak and assist to identify areas with significant conservation value.